(untitled) (The Journal of Nuwakot Adarsha Multiple Campus, 2025)
This study explores the theoretical foundations, historical development, and pedagogical implications of English for specific purposes (ESP) in the context of business communication. It critically examines the development of ESP from a linguistic and pragmatic reaction to globalization by addressing the specific communicative needs of professionals in the business sector. The review emphasizes on the significance of need analysis, genre theory, and discourse analysis in developing proper ESP curriculum. Special emphasis is considered on business English as a lingua franca, intercultural communication, and the expanding importance of corpus-based research in building learner-centered curriculum. Though the domain has made tremendous progress, there are still issues in integrating standardization with the various, real world demands of international corporate communication. This review suggests a more contextdriven, flexible, and integrated method of teaching ESP in business context.